Drug Supply Information System at Royal Prima Hospital - Dakhi, Odiliana; Rahmi, Elvika (Pascal: Journal of Computer Science and Informatics, 2023)
Drug Inventory Information System at Royal Prima Hospital Medan. The purpose of making this final project is to be able to assist agencies in finding drugs available at RSU Royal Prima Medan computerized or using a system, designing a system so that the drug search process can be easily found by employees of RSU Royal Prima. The data collection methods carried out by the author include the field method and the average method. The Drug Inventory Information System at Royal Prima Hospital uses VB.Net 2010 programming and MySQL as the database.